Chemical Characteristics of Croatian Traditional Istarski pršut (PDO) Produced from Two Different Pig Genotypes - Marina Krvavica; Dario Lasić; Jasenka Gajdoš Kljusurić; Jelena Đugum; Špiro Janović; Srđan Milovac; Jasna Bošnir (Molecules, 2021)
Chemical characteristics of raw and processed Istarski pršut (PDO) produced from two different pig genotypes were studied with special emphasis on amino and fatty acid composition and factors of lipid stability. Raw hams of Large White (LW)xLandrace (L), and (LWxL)xDuroc (D) pig genotypes were used in the study (20 hams of each genotype). All left raw hams from each carcass were processed in accordance with the PDO specification of Istarski pršut, and other half (the right ones) of LWxL)xD genotype were used for analyses of raw hams (fresh muscles). Istarski pršut was evaluated on the basis of the chemical parameters of the raw and matured lean ham. The process of dry curing significantly influenced the chemical properties of Istarski pršut. Despite the higher content of intramuscular fat and polyunsaturated fatty acids, the fat of (LWxL)xD ham was much more resistant to hydrolysis and oxidation, suggesting that fatty acid profile and other factors, also play a significant role. Significant differences between pig genotypes in the amino acid and fatty acid profiles were found. The analyzed Istarski pršut may be distinguished by prints of multivariate chemometric statistical analysis, based on their amino acid and fatty acid compositions.